PERANAN PERMAINAN TRADISIONAL ENGKLEK DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK USIA SEKOLAH DASAR DI DESA HAMPARAN PERAK - Lestari, Wiwik; Siregar, Nurdiana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This study aims to describe the traditional game played hopscotch elementary school children in the Hamparan Perak village. This study used a qualitative approach. The subjects were children of primary school age who live in the Hamparan Perak village. Data was collected by observation, interview, and documentation. The results of this study indicate that the traditional hopscotch game in Hamparan Perak village there are three forms of the scarecrow, box, and aircraft. Game hopscotch jump performed by each of the rectangular pattern is drawn with one leg bent and the foot is lifted. All four terms that have been bypassed by gacok, players have the opportunity to embellish the house in one of the boxes, by throwing gacok to one rectangle with the backs of hopscotch. Players who earn the most home wins stamp.Keywords : traditional games, social skills